Individual and collaborative technology-mediated learning using question & answer online discussion forums – perceptions of Public Health learners in Dubai, UAE. (2nd January 2016) - Awofeso, Niyi; Hassan, Moustafa; Hamidi, Samer
Abstract : This case study provides evidence-based suggestions for the use of Question and Answer discussion forums for improving quality and assessment of online learning. General online discussion forums are accessible at any time to all subscribers, making it possible for some learners to update, concur with or paraphrase discussions posted earlier by their peers or the tutors. Consequently, the usefulness of such forums in individual and constructivist learning is compromised, especially when 'correct' responses are posted early on by participants. The Question and Answer (Q & A) version of discussion forums significantly addresses such inadequacies by restricting access to forum subscribers until they have made a post. We focus on Public Health learners' perceptions of Q & A discussion forums implemented at Hamdan Bin Mohammed Smart University, UAE. Analyses of learners' perception surveys of 25 participating Master of Public Health learners and 8 Bachelor of Health Administration learners reveal that the Q & A discussion forum platform offers distinct advantages over general discussion forums in synergising individual and co-operative learning in Public Health training.